A commentary on drug safety and genomics: Promising new agents may require expansion of guidelines for subject screening in clinical trials. (12th July 2021) - Pressman, Peter; Clemens, Roger; Blackburn, Thomas; Hayes, A Wallace
The fatty acid amide hydrolase (FAAH) inhibitors likely represent a novel therapeutic yet complex target with the potential to impact various disease processes that present significant unmet medical needs. Despite a history of significant adverse events and still ill-defined risks associated with FAAH inactivation, potential clinical results of FAAH inhibitors for the management of human diseases suggest strongly that the research not be abandoned. In the present commentary we argue that the way to move forward safely and effectively may lie in universal expansion of clinical trials guidelines and toxicology protocols to include targeted genomic screening of clinical trial subjects. Generalization to the safety testing of many new pharmaceutical agents may be the silver lining of an otherwise dark cloud.